TEACHING SUBJECTS BEYOND EXPERTISE - CANOY, PRISCILLA F.; NATHANIEL GIDO; GILBERT JOHNMONTAJES; RENATO CANOY; AMANAH TUYOR (International Journal of Multidisciplinary Research and Studies, 2022)
The purpose of this study is to look into the social effects of teaching subjects that are outside the scope of the twenty-six (26) teachers at X-National High School. A modified survey questionnaire created by the researchers is organized into three distinct sections. It asks for information about the respondent's gender, age, educational background, and performance rating in Part 1. The answers to the problem stated are in Part II. In Part III, questions are asked on difficulties faced by teachers who taught two or more subjects and how they overcame those difficulties. Frequency and percentages are shown in Tables 1 through 5. With the use of the mean, standard deviation, and qualitative analysis, Tables 6 and 7 are interpreted. The ideas and opinions of the respondents were presented using qualitative analysis for difficulties 3 and 4. Based on the study's findings, it was discovered that professors tasked with instructing students on topics other than their own have difficulty. This results from the shortage of instructional resources, the short class hour, the accessibility of recent and high-quality books in the school library, and the production of the daily lesson log (DLL). Despite the fact that they were not experts in the subjects they taught, they accepted the position when the head of their school assigned it to them. Additionally, the difficulty of locating educational resources and instructional materials is lessened thanks to technology and the Internet. As a result, they concur that it is their responsibility to educate, and as such, they may effectively manage their time so as to be flexible in undertaking things other than teaching.